The Successful Use of Combined Extracorporeal Life Support in Treatment of the New Coronavirus Infection Complicated by the Development of Multiple Organ Dysfunction in a Pregnant Woman - M. А. Petrushin; E. V. Tereschenko; P. I. Melnichenko; E. A. Kudryashova; I. Yu. Starchenko; I. S. Nikiforov; T. V. Kirsanova; M. А. Babaev (Вестник анестезиологии и реаниматологии)
Pregnant and postpartum women are at a higher risk of infection with SARS-CoV-2 as well as a higher risk of adverse outcomes for the mother and fetus. Standard approaches to the management of COVID-19-associated multiple organ dysfunction may not always be implemented in this category of patients. In the clinical case of a patient, who developed multiple organ dysfunction syndrome (severe ARDS, coagulopathy) associated with COVID-19 in the postpartum period, we demonstrate the successful use of combined extracorporeal life support that included veno-venous extracorporeal membrane oxygenation, therapeutic plasma exchange and renal replacement therapy with the universal oXiris set.